1989
DOI: 10.1073/pnas.86.22.8847
|View full text |Cite
|
Sign up to set email alerts
|

In vivo rearrangement of mitochondrial DNA in Saccharomyces cerevisiae.

Abstract: A revertant (SPR1) from a high-frequency petite strain of Saccharomyces cerevisiae has been shown by mapping and sequence analysis to have a rearranged mitochondrial genome. In vivo rearrangement has occurred through a subgenomic-recombination pathway involving the initial formation of subgenomic molecules in nascent petite mutants, recombination between these molecules to form an intermediate with direct repeats, and subsequent excision of the resident or symposed duplication to yield a molecule with three no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 20 publications
0
7
1
Order By: Relevance
“…(9). This result contrasts with those of another study in which it was found that GC clusters of the al category are involved in the generation of different deletions (3). However, both sets of findings confirm the recombinogenic nature of GC clusters and indicate that mitochondrial recombinases involved in deletion exhibit some flexibility with regard to sequence specificity.…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…(9). This result contrasts with those of another study in which it was found that GC clusters of the al category are involved in the generation of different deletions (3). However, both sets of findings confirm the recombinogenic nature of GC clusters and indicate that mitochondrial recombinases involved in deletion exhibit some flexibility with regard to sequence specificity.…”
contrasting
confidence: 57%
“…Recent developments in manipulating the mitochondrial genome have enabled us to generate strains deleted for large segments of base-biased sequences (3,4). This has allowed us to examine whether some of these regions influence mitochondrial biogenesis.…”
mentioning
confidence: 99%
“…That the DSBs detected in this study occur around GC cluster C may not be surprising, since GC clusters of several sequence types in yeast mtDNA have been found to be recombinogenic (6,13,49). Further work is required to determine whether the transcription-dependent DSBs we have observed are correlated with recombination structures.…”
Section: Discussionmentioning
confidence: 80%
“…Subgenomic recombinations also take place at short and direct sequence repeats, a pattern consistent with the involvement of a recombination-excision mechanism. These events underlie the frequent generation of respiration-deficient petite mutants in S. cerevisiae, which stably transmits the extensively deleted Ϫ genomes (41)(42)(43). Similar repeat-mediated recombination events were seen in Neurospora crassa, which are manifested by the generation of plasmid-like supercoiled subgenomic circles in mitochondria (44).…”
Section: Mtdna Recombination In Yeastmentioning
confidence: 86%